Pengaruh Kepuasan Kerja terhadap Kinerja Karyawan PT Soho Global Health - Khairunnisa, Siska (BUDGETING : Journal of Business, Management and Accounting, 2024)
Human resources are a very important factor in an organization, both large and small scale organizations. Human resources are seen as a very determining element in the development of an organization, so the role of human resources is increasingly important. This research aims 1) to explain job satisfaction and performance of PT employees. Soho Global Health. 2) to determine the effect of job satisfaction on the performance of PT employees. Soho Global Health. The method used in this research is the research method using survey data with a questionnaire as a data collection tool, while the descriptive data analysis method used in this research is quantitative analysis. The research results show that: 1) Of the 51 respondents, they think that employee job satisfaction at PT. Soho Global Health has a high level of employee satisfaction and employee performance at PT. Soho Global Health has a high level of employee satisfaction. 2) There is a significant influence between the job satisfaction variable (X) and the performance variable (Y). This is proven by the value of tcount > ttable (6,849 > 2.026). Keywords: Employee Performance, Job Satisfaction, PT Soho Global Health.